Architektur immaterieller Arbeit - Rumpfhuber, Andreas (Turia und Kant, 2013)
The book takes up the (post-)operaist concept of immaterial labour (cf. Maurizio Lazzarato: 1998, Toni Negri, Michael Hardt: 2000) and relates it to spatial processes and architectural projects from the 1960s. The book's title is the hypotheses of its investigation. It allows to be exemplified with the following questions: Do we find, parallel to a dominant cultural practice of immaterial labour new forms and orders of architecture? Which forms does it take on? Or does workplace architecture disappear at all parallel to the blurring of the formerly clearly marked spaces of the factory?